Forty years of Anthropology Notebooks, heritage of the “María Eugenia Bozzoli Vargas” Ethnology Laboratory - Araya, María del C. (2022)
This document presents, a historical account of the journal Cuadernos de Antropología, of the University of Costa Rica, 1982-2021, together with an analysis of its academic production, according to authors and published articles. The work is based on qualitative and quantitative data, whose scope shows a gradual transformation process that turned this means of dissemination into an electronic publication. Since 2007 the articles have been available digitally and as of 2014, they can be consulted for free and immediately on the journal’s page. With this, access and visibility of information has been increased, which refers to work carried out in different parts of the world, mainly in Costa Rica. Even when there are investigations carried out by the specialties of anthropology, social anthropology and archeology dominate. It is concluded that it is necessary to propose strategies that increase research all the specialities of anthropology in the geography of interest of the journal: Central America, southern Mexico, insular Caribbean and northwestern Colombia. Furthermore, Cuadernos de Antropología has the challenge of becoming a platform for the development of academic communities that impact the discipline and social reality.